IMPLEMENTASI MODUL MARKERLESS TRACKING PADA PENGENALAN SISTEM PENCERNAAN - Geofanny, Tya Agnesya; Hikmatyar, Missi; Sundari, Shinta Siti (Institut Teknologi dan Bisnis Swadharma, 2024)
The age of technology cannot be denied that education also presents technology in learning. There are problems in the conventional learning process, where teachers tend to be active while students tend to be passive as seen from the results of student exams which on average get scores in the